2020
DOI: 10.3389/fpls.2020.581666
|View full text |Cite
|
Sign up to set email alerts
|

Dark-Induced Hormonal Regulation of Plant Growth and Development

Abstract: The sessile nature of plants has made them extremely sensitive and flexible toward the constant flux of the surrounding environment, particularly light and dark. The light is perceived as a signal by specific receptors which further transduce the information through the signaling intermediates and effector proteins to modulate gene expression. Signal transduction induces changes in hormone levels that alters developmental, physiological and morphological processes. Importance of light for plants growth is well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 121 publications
(173 reference statements)
2
18
0
Order By: Relevance
“…COP1 mediates HY5 degradation in the dark, whereas light blocks the interaction of COP1 with HY5, consequently promoting the accumulation of HY5 and the transcriptional activation of its downstream target genes [36]. Light and dark conditions also alter phytohormone responses, as light facilitates auxin transport from the shoot apex to the root [37], while darkness induces the expression of phytohormone biosynthesis and signaling-related genes for ethylene and gibberellic acid, which regulate skotomorphogenic development [50]. Analysis of MSD2 expression in a cop1-4 mutant allele showed that COP1 negatively regulates MSD2 expression in the dark but had no effect on MSD2 expression in the light (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…COP1 mediates HY5 degradation in the dark, whereas light blocks the interaction of COP1 with HY5, consequently promoting the accumulation of HY5 and the transcriptional activation of its downstream target genes [36]. Light and dark conditions also alter phytohormone responses, as light facilitates auxin transport from the shoot apex to the root [37], while darkness induces the expression of phytohormone biosynthesis and signaling-related genes for ethylene and gibberellic acid, which regulate skotomorphogenic development [50]. Analysis of MSD2 expression in a cop1-4 mutant allele showed that COP1 negatively regulates MSD2 expression in the dark but had no effect on MSD2 expression in the light (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mutants with defects in any of these repressor proteins display constitutive photomorphogenic (COP) phenotypes under dark conditions ( Lau and Deng, 2012 ). The repressor proteins are characterized into four categories with overlapping functions and have been studied extensively ( Deepika et al, 2020 ; Pham et al, 2020 ). The first one is COP1, which is a RING-finger-type ubiquitin E3 ligase ( Deng et al, 1992 ).…”
Section: Light As An Environmental Cuementioning
confidence: 99%
“…Furthermore, it can influence growth and developmental processes, including different metabolic pathways in plant–pathogen interactions (Purschwitz, Müller, Kastner, & Fischer, 2006; Thind & Schilder, 2018; Tisch & Schmoll, 2010; van der Horst, Key, & Hellingwerf, 2007). In contrast to optimal light conditions, high and low light intensity, including darkness, induce different signalling and regulation pathways modulated by phytohormones, especially jasmonic acid (JA) and salicylic acid (SA) (Ballaré, 2014; Deepika, Sagar, & Singh, 2020; Roberts & Paul, 2006).…”
Section: Light Sensing and Plant Responsesmentioning
confidence: 99%
“…Various phytohormones play a role in the regulation of plant defence responses depending on the light (Ballaré, 2014; Deepika et al, 2020; Roberts & Paul, 2006). SA is required to establish both local and systemic acquired resistance after pathogen infection.…”
Section: The Role Of Light and The Key Defence‐related Phytohormones In Plantsmentioning
confidence: 99%